Analisis Kepuasan Penyedia Terhadap Penerapan Prinsip Efisien, Efektif, Transparan, dan Terbuka Pada Pengadaan Konstruksi Pemerintah di Kabupaten Manggarai - Sandi, Patrisius Valdoni; Kaur, Ewaldus Onesiaus; Handayani, Lulu (Universitas Dr. Soetomo, 2024)
Supplier satisfaction in Public Procurement (PBJP) can significantly impact project execution quality, efficiency and productivity, reputation and long-term relationships, innovation, and risk management. This is especially important in Manggarai Regency, where construction projects often focus on accessibility and connectivity. Therefore, an analysis of supplier satisfaction with the application of efficient, effective, transparent, and open principles in government construction procurement is needed to determine priority improvements for the existing indicators within these principles. The results of the suitability level analysis (Tki) show a suitability value of 96.79% between performance and importance in applying efficient, effective, transparent, and open principles, indicating that the service quality provided is lacking or does not meet what is considered important by the suppliers, or in other words, it is not yet satisfactory. A satisfaction analysis using the Customer Satisfaction Index (CSI) method yielded a CSI value of 61.917%, which falls within the range of 66%-80.99%, indicating that respondents are generally satisfied with the application of these principles in government construction procurement in Manggarai Regency.